Qingwenzhike Prescription Alleviates Acute Lung Injury Induced by LPS via Inhibiting TLR4/NF-kB Pathway and NLRP3 Inflammasome Activation - Zhang, Cai; Wang, Xinran; Wang, Chunguo; He, Cheng; Ma, Quantao; Li, Jialin; Wang, Weiling; Xu, Yan-Tong; Wang, Ting (Frontiers in Pharmacology, 2021)
Background: Acute lung injury (ALI) is characterized by dysfunction of the alveolar epithelial membrane caused by acute inflammation and tissue injury. Qingwenzhike (QWZK) prescription has been demonstrated to be effective against respiratory viral infections in clinical practices, including COVID-19 infection. So far, the chemical compositions, protective effects on ALI and possible anti-inflammatory mechanisms remain unknown. Methods: In this study, the compositions of QWZK were determined via the linear ion trap/electrostatic ﬁeld orbital trap tandem high-resolution mass spectrometry (UHPLC-LTQ-Orbitrap MS). To test protective effects of QWZK on ALI, an ALI model induced by lipopolysaccharide (LPS) in rats was used. The effects of QWZK on the LPS-induced ALI were evaluated by pathological changes and the number and classification of white blood cell (WBC) in bronchoalveolar larage fluid (BALF). To investigate the possible underlying mechanisms, the contents of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein (MCP-1), interleukin-1β (IL-1β), interleukin-18 (IL-18) and immunoregulatory related factors interferon-γ (IFN-γ) were detected by ELISA. Further, the expression of Toll-like receptor 4 (TLR4), p-IKKα/β, IKKα, IKKβ, p-IκBα, IκBα, p-NF-κB, nuclear factor-κB (NF-κB), NOD like receptor family pyrin domain containing 3 (NLRP3), cleaved-Caspase-1, pro-Caspase-1, apoptosis-associated speck-like protein containing CARD (ASC) and β-actin were tested by Western blot. Results: Total 99 compounds were identified in QWZK, including 33 flavonoids, 23 phenolic acids, 3 alkaloids, 3 coumarins, 20 triterpenoids, 5 anthraquinones and 12 others. ALI rats induced by LPS exhibited significant increase in neutrophile, significant decrease of lymphocyte, and evidently thickener alveolar wall than control animals. QWZK reversed the changes in WBC count and alveolar wall to normal level on the model of ALI induced by LPS. ELISA results revealed that QWZK significantly reduced the over-expression of pro-inflammatory factors IL-6, TNF-α, MCP-1, IL-1β, IL-18 and IFN-γ induced by LPS. Western blot results demonstrated that QWZK significantly down-regulated the over-expression of TLR4, p-IKKα/β, p-IκBα, p-NF-κB, NLRP3, cleaved-Caspase-1 and ASC induced by LPS , which suggested QWZK inhibited TLR4/ NF-κB signaling pathway and NLRP3 inflammasomes. Conclusions: The chemical compositions of QWZK were